A Study in Prediction of Food Grain Prospects in Rajasthan - Kalla, Jagdeesh C; Dixit, Brij M (Annals of Arid Zone, 2016)
The problem of imbalance between demand for and supply of food gains calls for a deeper probe at regional levels to planners to allocate planned resources more efficiently. Demand for and supply of food grain aggregates wee estimated from the relevant data published by Government of Rajasthan from time to time. Short-term predictions of demand and supply of food grain aggregate revealed, contrary to a general belief, that supply of food grains are likely to lead comfortably the demand for the same, on Rajasthan. The projected quantities of aggregates were decomposed for comparison between predicted demand for supply of food grains. It was revealed that Rajasthan is likely to be surplus producer in case fo Bajra, Jowar, Maize and Gram and deficit producer in case of Rice, Wheat and small millets. It appears, on the face of the study, that problems of scarcity of meet the demand in Rajasthan crop up not mainly due to shorter supply as that of inefficient distribution.